An improved preparation of mesoporous silica‐supported Pd as sustainable catalysts for phosphine‐free Suzuki–Miyaura and Heck coupling reactions. (23rd August 2013) - Basu, Basudeb; Paul, Susmita
<x xml:space="preserve">Abstract</x> An improved and eco‐friendly procedure has been developed to generate mesoporous silica‐supported palladium nanoparticles (SiO2@PdNP) that could be used as a sustainable heterogeneous Pd catalyst for phosphine‐free Suzuki–Miyaura and Heck coupling reactions with excellent turnover number and turnover frequency. The presence of Pd on the silica surface was detected by X‐ray diffraction and the structural morphology of SiO2@PdNP was obtained by transmission electron microscopy. The heterogeneous catalytic system is recyclable and leaching of the metal after the reaction is not apparently observed. Copyright © 2013 John Wiley & Sons, Ltd.